PENGARUH KINERJA PEGAWAI DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi kasus pada Badan Pengelola Keuangan dan Aset Daerah Kabupaten Sikka) - Fransiscus De Romario; Yoseph Darius Purnama Rangga; Yohana Erlin (Jurnal Accounting UNIPA, 2022)
This study aims to improve performance in agencies and further develop knowledge and test the effect of employee performance and the use of information technology on the timeliness of financial reporting. This type of research is descriptive and quantitative research. The population in this study is the number of all employees divided into several divisions with a total of 50 employees. The sampling technique using the Saturated Sampling technique with the number of samples used was 37 respondents taken based on the returned questionnaire. Data collection was carried out using a questionnaire measured with a Likert Scale. The analysis methods used are Multiple Linear Regression Analysis, T Hypothesis Test, F Hypothesis Test and Coefficient of Determination. The results showed that employee performance has a significant effect on the timeliness of financial reporting. The use of information technology has a significant effect on the timeliness of financial reporting. For related agencies, in order to improve performance in agencies and further develop the use of information technology so that financial management and reporting can be even better. Keywords : Employee Performance, Utilization of Information Technology, Timeliness of Financial  eporting.